Analysis of Patterned Defects on Graphene Using Micro-Raman Spectroscopy and Liquid Crystals. (13th April 2015) - Yang, Gwangseok; Oh, Sooyeoun; Kim, JiHyun
Abstract : In this work, we report a facile probing method for large-area graphene. Patterned defects in graphene were defined by means of photolithography and oxygen plasma treatment. Defect level was characterized using micro-Raman spectroscopy. Only defined region was exposed to oxygen plasma while almost no change is observed in PR remained region. The patterned defects in graphene were visualized using polarized optical microscopy with nematic liquid crystal. Differently aligned textures of liquid crystal result in distinct optical variations.